Prolonged cooling of andesitic-dacitic lava flows produces optimal groundmass material for 40Ar/39Ar dating - Chris E. Conway; Andrew T. Calvert; Osamu Ishizuka; Seiko Yamasaki; Isoji Miyagi; Yumiko Harigane; Graham S. Leonard (Chemical Geology, 2026)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Paleomagnetically defined brief lifespans for two large shield volcanoes in the Cascades Arc - Anthony F. Pivarunas; Dawnika L. Blatter; L.J. Patrick Muffler; Michael A. Clynne; Andrew T. Calvert; Lauren N. Harrison; Robert L. Christiansen (Journal of Volcanology and Geothermal Research, 2023)

Precaldera Mafic Magmatism at Long Valley, California: Magma-Tectonic Siting and Incubation of the Great Rhyolite System - Wes Hildreth; Judy Fierstein; Andrew T. Calvert (Journal of Volcanology and Geothermal Research, 2023)

Short‐term movement dynamics of the world’s largest sea cucumbers (genus Thelenota ) - Benjamin C. T. Gray; Luke A. Calvert; Steven W. Purcell (Marine Ecology, 2022)
Movement studies on marine animals can inform conservation and fishery management planning through data that explain likely dispersals and home‐ranging behaviours. Relatively few studies are documented for exploited marine invertebrates, despite many having a high ecological and commercial value. We assessed the diurnal movement patterns of Thelenota ananas and Thelenota anax , the world's largest sea cucumbers, which are highly exploited throughout the Indo‐Pacific. At two coral reef sites at Lizard Island, northern Australia, we tracked the 2‐hourly displacement of individuals from morning to nightfall. Movement of T . ananas was more reef‐associated and tortuous than T . anax . Displacement rates averaged 80 cm h −1 (±8 SE) for T . ananas and 73 cm h −1 (±20) for T . anax . Body size accounted for half of the variation in displacement for T . ananas . Mobility peaked in the late afternoon or early evening for both species, and animals tended to reverse their direction of travel after midday. The data reflect a pattern of animals meandering out from their reef shelters onto sandy lagoon floors to forage, before returning to the reefs. This empirical evidence offers further support that these holothuroids contribute to the formation of “reef halos”. The exceptionally high movement rates and patterns found in this study should inform the design of spatial management measures.

Compaction- and Shear-Induced Well Deformation in Tyra: Geomechanics for Impact on Production - P. M. T. M. Schutjens; P. Fokker; U. B. B. Rai; J. Kandpal; M. V. Cid Alfaro; N. D. Hummel; R. Yuan; F. Klever; S. De Gennaro; J. Vaibav; F. Bourgeois; M. Calvert; et al. (Rock Mechanics and Rock Engineering, 2019)

Multi-scenario Geomechanical Modeling for Investigating Well Deformation in the Deep Overburden Over a Compacting Reservoir in the North Sea - R. S. Yuan; M. A. Calvert; P. M. T. M. Schutjens; F. G. Bourgeois (Rock Mechanics and Rock Engineering, 2019)

Timescales of magmatic differentiation from alkali basalt to trachyte within the Harrat Rahat volcanic field, Kingdom of Saudi Arabia - Mark E. Stelten; Drew T. Downs; Hannah R. Dietterich; Gail A. Mahood; Andrew T. Calvert; Thomas W. Sisson; Hani Zahran; Jamal Shawali (Contributions to Mineralogy and Petrology, 2018)

Lava-ice interaction on a large composite volcano: a case study from Ruapehu, New Zealand - C. E. Conway; D. B. Townsend; G. S. Leonard; C. J. N. Wilson; A. T. Calvert; J. A. Gamble (Bulletin of Volcanology, 2015)

Reply to the comment on the article “40Ar/39Ar dating of tuff vents in the Campi Flegrei caldera (southern Italy): toward a new chronostratigraphic reconstruction of the Holocene volcanic activity” by Isaia et al. - L. Fedele; D. D. Insinga; A. T. Calvert; V. Morra; A. Perrotta; C. Scarpati (Bulletin of Volcanology, 2012)

40Ar/39Ar dating of tuff vents in the Campi Flegrei caldera (southern Italy): toward a new chronostratigraphic reconstruction of the Holocene volcanic activity - L. Fedele; D. D. Insinga; A. T. Calvert; V. Morra; A. Perrotta; C. Scarpati (Bulletin of Volcanology, 2011)

Age, geochemical composition, and distribution of Oligocene ignimbrites in the northern Sierra Nevada, California: implications for landscape morphology, elevation, and drainage divide geography of the Nevadaplano - Elizabeth J. Cassel; Andrew T. Calvert; Stephan A. Graham (International Geology Review, 2009)

Postshield stage transitional volcanism on Mahukona Volcano, Hawaii - David A. Clague; Andrew T. Calvert (Bulletin of Volcanology, 2009)

Continuation of the New England Orogen, Australia, beneath the Queensland Plateau and Lord Howe Rise - N. Mortimer; F. Hauff; A. T. Calvert (Australian Journal of Earth Sciences, 2008)

Comparison of in vitro cytotoxicity of Fusarium mycotoxins,deoxynivalenol, T-2 toxin and zearalenone on selected human epithelial cell lines - T. W. Calvert; K. E. Aidoo; A. G. G. Candlish; A. R. Mohd. Fuat (Mycopathologia, 2005)

North Atlantic phylogeography and large‐scale population differentiation of the seagrass Zostera marina L. - JEANINE L. OLSEN; WYTZE T. STAM; JAMES A. COYER; THORSTEN B. H. REUSCH; MARTIN BILLINGHAM; CHRISTOFFER BOSTRÖM; ELIZABETH CALVERT; HARTVIG CHRISTIE; STEPHEN GRANGER; RICHARD LA LUMIÈRE; NATALIYA MILCHAKOVA; MARIE‐PIERRE OUDOT‐LE SECQ; et al. (Molecular Ecology, 2004)
As the most widespread seagrass in temperate waters of the Northern Hemisphere, Zostera marina provides a unique opportunity to investigate the extent to which the historical legacy of the last glacial maximum (LGM18 000–10 000 years bp ) is detectable in modern population genetic structure. We used sequences from the nuclear rDNA–internal transcribed spacer (ITS) and chloroplast mat K‐intron, and nine microsatellite loci to survey 49 populations (> 2000 individuals) from throughout the species’ range. Minimal sequence variation between Pacific and Atlantic populations combined with biogeographical groupings derived from the microsatellite data, suggest that the trans ‐Arctic connection is currently open. The east Pacific and west Atlantic are more connected than either is to the east Atlantic. Allelic richness was almost two‐fold higher in the Pacific. Populations from putative Atlantic refugia now represent the southern edges of the distribution and are not genetically diverse. Unexpectedly, the highest allelic diversity was observed in the North Sea–Wadden Sea–southwest Baltic region. Except for the Mediterranean and Black Seas, significant isolation‐by‐distance was found from ~150 to 5000 km. A transition from weak to strong isolation‐by‐distance occurred at ~150 km among northern European populations suggesting this scale as the natural limit for dispersal within the metapopulation. Links between historical and contemporary processes are discussed in terms of the projected effects of climate change on coastal marine plants. The identification of a high genetic diversity hotspot in Northern Europe provides a basis for restoration decisions.

Three-dimensional mapping of a landslide using a multi-geophysical approach: the Quesnel Forks landslide - A. Bichler; P. Bobrowsky; M. Best; M. Douma; J. Hunter; T. Calvert; R. Burns (Landslides, 2004)

HLA-B*4034 identified in a UK Caucasoid potential bone marrow donor - Steven T Cox; Franco Tavarozzi; Alasdair McWhinnie; Michael A Hoddinott; Anthony Calvert; Finnuala Baker; J. Alejandro Madrigal; Ann-Margaret Little (Immunogenetics, 2001)

Effect of dietary selenium on the response of stressed and unstressed chickens toEscherichia coli challenge and antigen - Calvert T. Larsen; Frank W. Pierson; Walter B. Gross (Biological Trace Element Research, 1997)